Peran Pesantren sebagai Arena Konstruksi Sosial Keagamaan: Studi Kasus Baiat Santri di SMA Plus Muallimin 182 Rajapolah - Ana Aulia Hanifah (CV. ITTC INDONESIA, 2025)
This study examines the role of Islamic boarding schools (pesantren) as an arena for religious social construction through a case study of the practice of bai'at santri (students' pledge of allegiance) at SMA Plus Muallimin 182 Rajapolah. Pesantren, as a traditional Islamic educational institution, not only functions as a place for the transfer of religious knowledge, but also as a space for the formation of the religious and social identity of students. The practice of bai'at, as a ritual of loyalty and spiritual commitment, becomes an important momentum in the process of constructing religious awareness of students that distinguishes it from formal educational institutions in general. Using a qualitative approach with a case study method, the study explores the meaning and implications of the bai'at practice on the formation of character and religious orientation of students. Data were collected through in-depth interviews with ustaz and analysis of Islamic boarding school documents. The theoretical framework used is the social construction theory of Peter L. Berger and Thomas Luckmann to understand how religious reality is formed, maintained, and internalized in the context of Islamic boarding schools. The results show that bai'at santri at SMA Plus Muallimin 182 Rajapolah is a systematic institutional mechanism in shaping collective religious awareness. Through the process of externalization, objectification, and internalization, Islamic values, spiritual ties with the ustaz, and commitment to the traditions of the Islamic boarding school are firmly embedded in the students.